L’insegnamento “ereticale” sulla visione di Dio nelle opere di Giuseppe Hazzāyā, mistico siro-orientale del secolo VIII - Havrylyk, Ihnatia (Vox Patrum, 2018)
In the history of the Assyrian Church of the East the VIII century was a period of the flourishing of monastic mysticism. One of the great spiritual fathers of the period was Joseph Hazzāyā who made a synthesis of all spiritual and mystical experiences of his predecessors. In his writings he basically holds to the teachings on the vision of God, which was strange to the Antiochene tradition and therefore condemned as heretical by Timothy I, the patriarch of the Church of the East at the synod of 786-787. In this article the author analyzes Joseph’s teachings on the vision of God, striving to comprehend valid reasons why they deserve to be considered heretical. Furthermore the following pages contain overview of terms used by Joseph when he refers to the experience of divine vision and with special emphasis on the particulars of his teachings. The last paragraph presents a brief survey of the Christological doctrine of the Church of the East and its opinion on the experience of the vision of God.